The Evolution of Tariff Protection and Wage Protection in the Late Colonies and Early Federation1. Issue 4 (20th July 2017) - Lloyd, Peter
Abstract : This paper examines the links between tariff protection and wage protection. These two areas of regulation were linked politically by a coalition of the Protectionist Party and the Labour Party which supported both policies together. In the regulatory systems themselves there were links through New Protection Policy and the major influence it had on the hugely important Harvester Judgment of the Court of Conciliation and Arbitration. By 1910, these developments had laid down the foundations of Australian tariff policy and labour market regulation which became among the most highly regulated markets in the non‐communist world for many decades.